Alfabetização e letramento: uma proposta pedagógica sobre a interrelação desses processos a partir do texto como eixo da aprendizagem nos anos iniciais do ensino fundamental - Costa, Neyliane Barros (2024)
This work entitled "LITERACY AND LITERACY: a pedagogical proposal on the interrelationship of these processes from the text as an axis of learning in the early years of elementary school, at the Ferdnan Gutman Municipal School, in Santa Inês, MA", starts from the challenges of working on literacy and literacy as interrelated processes to develop autonomous-reflexive subjects in social contexts. This study highlights in an integrated way the historical trajectory and the distinction between literacy and literacy, emphasizing the relevance of these two processes over time in the formation of readers. In the educational context, currently, difficulties still persist on how to stimulate students' interest in reading, understanding and interpreting text in the teaching-learning process. In view of this, this study sought to use textual genres to stimulate reading in the classroom, aiming to make classes more dynamic and keep students more integrated into the process, thus contrasting the idea that learning is the process of mere acquisition of codes and symbols via memorization. The final considerations of this work address the challenges of literacy and literacy in the Brazilian educational context, highlighting the importance of these interrelated processes in the early years of elementary school. The text is presented as a central axis of learning, highlighting the need for an approach that uses different textual genres to promote integral formation. The research emphasizes that literacy should go beyond simple decoding, encompassing reading, comprehension and text production skills. Family participation is recognized as fundamental, creating a favorable environment for learning. The proposed activities showed that working with different textual genres results in a more dynamic and integrated learning, expanding the linguistic and cultural repertoire of the students. The conclusion reinforces the importance of a continuous and collaborative pedagogical approach between school, family and society, aiming at a critical and reflective education that enables students to become autonomous and critical citizens.